2020
DOI: 10.4102/sajbm.v51i1.1726
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between human resource management practices and organisational citizenship behaviour

Abstract: This study aims at providing empirical evidence on the extent to which organisational commitment mediates and strengthens the relationship between human resource management practices and organisational citizenship behaviour amongst administrative staff working in Jordanian universities.Design/methodology/approach: Data were gathered using a questionnaire. The population of the study consisted of administrative staff working at 29 universities. A total of 350 employees participated in the study. Data analysis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…Therefore, this study recommends that Jordanian industrial corporations must avoid weakness in management, and the shortage of facilities, using modern methods in training HR for SF and HW that used in industrial corporations to achieve a better OP. They must also adopt administrative procedures that dictate their goal, especially in the field ISC, which is reflected positively on the OP of industrial corporations if they implemented it in the right way [51], [63], [138], [140].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this study recommends that Jordanian industrial corporations must avoid weakness in management, and the shortage of facilities, using modern methods in training HR for SF and HW that used in industrial corporations to achieve a better OP. They must also adopt administrative procedures that dictate their goal, especially in the field ISC, which is reflected positively on the OP of industrial corporations if they implemented it in the right way [51], [63], [138], [140].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Ahmed (2016) amongst banking staff in Sudan found that high compensation contributes to higher organisational citizenship behaviour. Similarly, a study conducted by Owor (2016) in selected firms in Uganda and another conducted by Tashtoush and Eyupoglu (2020) amongst administrators in Jordanian universities revealed that fair compensation is a significant predictor of organisational citizenship behaviour. Contrary to this, Patil and Ramanjaneyalu (2018) revealed that compensation has no significant impact on organisational citizenship behaviour.…”
Section: The Relationship Between Compensations and Organisational Citizenship Behaviourmentioning
confidence: 92%
“…Research on the influence of compensation and training and development on organisational citizenship behaviour is not new. However, the studies were carried out in different sectors such as telecommunications and banking (Ahmed, 2016;Ibrahimet al, 2013;Jahan, 2015) outside South Africa (Tashtoush & Eyupoglu, 2020). Little is known about citizenship behaviour in the higher education sector in general and in South African rural-based institutions of higher learning in particular.…”
Section: Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations